Exploring communication between the thalamus and cognitive control-related functional networks in the cerebral cortex. - Wen, Xiaotong; Li, Wen; Liu, Yuan; Liu, Zhenghao; Zhao, Ping; Zhu, Zhiyuan; Wu, Xia (Cognitive, Affective & Behavioral Neuroscience, 2021)
It has been suggested by multiple studies (postmortem studies, invasive animal studies, and diffusion tensor imaging in the human brain) that the thalamus is important for communication among cortical regions. Many functional magnetic resonance imaging (fMRI) studies, including noninvasive and whole-brain studies, have reported thalamic co-activation with several cognitive control-related cortical systems. This forms a complex network that may be important for advanced cognitive control-related processes, such as working memory and attention. Nevertheless, how the thalamus communicates with the cognitive control-related network in the intact human brain is an essential question and needs further investigation. To address this question, we conducted a study using dynamic functional connectivity analysis and effective connectivity analysis based on fMRI data from young, healthy adult participants. The results showed that the middle thalamus exhibited both high in- and out-degree regarding the complex network related to cognitive control during both rest and task conditions. Furthermore, intrinsic communication via the middle thalamic regions showed dynamically co-varying patterns, and the thalamic regions showed high flexibility in dynamic community analysis. These results indicated that the mid-thalamic region is an important station for communication between nodes in cognitive control-related networks.